(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article examines some of the trends in the semantic derivation that actively operate in the literary and vulgar Ukrainian language at the beginning of the XXI century on discourse material of Ukrainian media. The semantic neologisms which are arisen from expansion of the semantic structure of native and loan words mainly on the basis of metaphor and metonymy are characterized.